Thermomechanical effects in the torsional actuation of twisted nylon 6 fiber. Issue 47 (30th July 2017) - Aziz, Shazed; Naficy, Sina; Foroughi, Javad; Brown, Hugh R.; Spinks, Geoffrey M.
ABSTRACT: Thermally induced torsional and tensile actuators based on twisted polymeric fibers have opened new opportunities for the application of artificial muscles. These newly developed actuators show significant torsional deformations when subjected to temperature changes, and this torsional actuation is the defining mechanism for tensile actuation of twisted and coiled fibers. To date it has been found that these actuators require multiple heat/cool cycles (referred to as "training" cycles) prior to obtaining a fully reversible actuation response. Herein, the effect of annealing conditions applied to twisted nylon 6 monofilament is investigated and it is shown that annealing at 200 °C eliminates the need for the training cycles. Furthermore, the effect of an applied external torque on the torsional actuation is also investigated and torsional creep is shown to be affected by the temperature and load. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45529. Abstract :